(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, general statistics of imitation words available in the “Annotated Dictionary of the Uzbek language” (volumes 2 and 5) are given and different approaches related to their meaning and interpretation are compared. Also, the places where words with similar meaning are indicated with a symbol as a reference to imitation words are highlighted